Legal regime as a form of regulation of industrial safety - Sirant, Myroslava; Matulkina, Olga (Global Prosperity, 2022)
The article considers the legal regime as a form of regulation of industrial safety. The methodological basis of the research is the method of system analysis and the functional approach to the study of legal phenomena. The topicality of the topic is due to the need for a rational, legal and effective use of the relevant legal regimes for regulating industrial safety, but also for the protection of rights and freedom - the right to life and safety, which are important values of the state. It is noted that the use of a functional approach to the definition of the legal regime allows to consider the legal regime in dynamics, to highlight its structural elements. The legal regime means a special order of legal regulation, which is put into effect for specific reasons, taking into account the uniqueness of the social situation and is not applied in that form in other spheres. Perception of the legal regime exclusively as a set of norms or institutions of law, on the contrary, significantly impoverishes the content, turns it into a static phenomenon, equates it with a group of legal norms fixed in a normative legal act. Implementation of public administration is impossible without the establishment of administrative and legal regimes in certain spheres of social reality. The content of the administrative and legal regimes for ensuring industrial safety is determined by a set of rules regulated by the norms of administrative law. Regime organization of management provides a regime that determines the legal status of the subject of management. The administrative-legal regime of industrial safety of high-risk facilities provides for and allows the regulation of relations arising under regime conditions by the norms of other branches of law. In this sense, there is every reason to talk about complex legal regimes in the field under investigation, in which the administrative-legal regime acts as one of the elements of a complex regime-legal formation.